Health-related quality of life in children and adolescents with sickle cell disease (Research, Society and Development, 2020)
To assess the health-related quality of life of children and adolescents with sickle cell disease (SCD). This is a cross-sectional study carried out with 97 male and female patients aged 5 to 18 years with clinical and laboratory diagnosis of SCD, seen at the Hematology and Hemotherapy Hospital of Pernambuco. The Pediatric Quality of Life InventoryTM questionnaires, version 4.0 – child/adolescent report – were applied. Most patients were female (76.3%), had sickle cell anemia (89.7%) and mixed race (59.8%). There was a significant association in the psychosocial domain between age groups 5 to 7 (72.10) and 8 to 12 years (p≤0.05), the latter of which had the worst quality of life score (65.36). There were significant differences between sexes only in patients aged 13 to 18 years for physical functioning and for the overall mean of the domains. The means in both cases were higher in female patients than in male ones (70.89 x 56.88 for physical functioning and 71.72 x 59.77 for the overall mean of the domains). Poor quality of life was observed among children and adolescents with SCD, with negative impacts according to age and sex.